2003
DOI: 10.1002/rcm.1019
|View full text |Cite
|
Sign up to set email alerts
|

Liquid chromatography/tandem mass spectrometry for the identification and determination of trichothecenes in maize

Abstract: A reliable, sensitive and selective liquid chromatography/tandem mass spectrometry (LC/MS/MS) method has been developed to determine four trichothecene mycotoxins (nivalenol, deoxynivalenol, fusarenon X and 3-acetyldeoxynivalenol) in maize. Sample preparation was performed by extracting the analytes with a mixture of acetonitrile and water, followed by a solid-phase extraction with Carbograph-4 cartridges as the purification step. For the LC/MS/MS analysis two interfacing systems, Turbo IonSpray (TISP) and atm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 29 publications
2
35
0
Order By: Relevance
“…In accordance to literature data (RazzaziFazeli 1999(RazzaziFazeli , 2002Zö llner et al 1999;Lau et al 2000;Lagana et al 2003), electrospray with negative ionization proved to be applicable more widely than with positive ionization. Negatively charged molecular ions of type B-trichothecenes (NIV, DON, ADON, FX) were detected by far more sensitively than their positively charged analogues.…”
Section: Investigations Of Mass Spectrometric Parameterssupporting
confidence: 80%
See 2 more Smart Citations
“…In accordance to literature data (RazzaziFazeli 1999(RazzaziFazeli , 2002Zö llner et al 1999;Lau et al 2000;Lagana et al 2003), electrospray with negative ionization proved to be applicable more widely than with positive ionization. Negatively charged molecular ions of type B-trichothecenes (NIV, DON, ADON, FX) were detected by far more sensitively than their positively charged analogues.…”
Section: Investigations Of Mass Spectrometric Parameterssupporting
confidence: 80%
“…The comparison shows a six to 17 times higher response when the ESI interface is used. Lagana et al (2003) reported similar results for an older type of the API Instrument (API 365), while Berthiller et al (2005) received the best results using the APCI interface in combination with an ammonia acetate buffer.…”
Section: Investigations Of Mass Spectrometric Parametersmentioning
confidence: 73%
See 1 more Smart Citation
“…7,18,19 More recently some methods have been developed using the liquid chromatography/tandem mass spectrometry for identification and determination of trichothecenes type A and B. 20,21 Despite of this, GC-MS is specially appropriate for its capability for simultaneous detection of trichothecenes from the groups A and B and for providing unequivocal identification.…”
Section: Introductionmentioning
confidence: 99%
“…In a very recent study, the analysis of four type B trichothecenes (NIV, DON, FUSX, 3-ADON) was performed in maize by an LC/MS/MS technique, comparing the commonly used Atmospheric Pressure Chemical Ionization (APCI) interface to the TurboIonSpray (TISP) interface in both negative and positive ion modes (Laganà et al, 2003). The most valuable spectra for each trichothecene were obtained using the turbo ion spray TISP-ESI system in the negative ion mode, gradient elution from water/methanol/acetonitrile 90:3:7 to water/methanol/ acetonitrile 20:24:56, with no modifier.…”
Section: B Liquid Chromatography/mass Spectrometry Determination Of mentioning
confidence: 99%